Rethinking Anti-Corruption Law Enforcement in Indonesia: A Critical Analysis of the Tom Lembong Case - Romdoni, Muhamad; Nathasya, Nathasya (LEGAL BRIEF, 2025)
Corruption remains a persistent and deeply rooted challenge within Indonesia’s legal and economic frameworks. It typically manifests through the intentional misuse of authority for personal or collective gain, often leading to substantial state financial losses. This study highlights the case of Thomas Trikasih Lembong (Tom Lembong), who allegedly issued a sugar import permit without following proper procedural protocols, particularly bypassing coordination meetings—an act that resulted in state losses exceeding IDR 578 billion. Despite occurring in 2016, significant delays in legal action—where one suspect was only apprehended in late 2024 and another in early 2025—underscore critical deficiencies in Indonesia’s legal enforcement mechanisms. Utilizing a normative juridical approach grounded in secondary data and analyzed through descriptive-analytical methods, this research demonstrates the urgency of reforming law enforcement practices. The prolonged impunity in high-profile corruption cases not only hampers justice but also erodes public trust in the rule of law. Therefore, systemic strengthening of Indonesia’s legal apparatus is imperative to ensure accountability and prevent future misuse of authority